Nationalism, Marxism, and African American literature between the wars : a new Pandora's box - Dawahare, Anthony, 1961- (Margaret Walker Alexander series in African American studies., 2003)
During and after the Harlem Renaissance, two intellectual forces nationalism and Marxism clashed and changed the future of African American writing.